Koncept zelenih knjižnic in prva primera njegove vpeljave pri nas - Zdravje, Ana (Knjižnica, 2019)
The article presents the green library concept, its beginnings and development throughout the world and in Slovenia. The article consists of two parts. The first part describes the course of development of the green library concept, based on a review of green library literature. This is followed by a presentation of the selected examples of such libraries. The second part highlights in detail the first two green libraries established in Slovenia. These two examples allow for a comparison of how a project based on the same concept was carried out differently in two respective regions of Slovenia, how the goals and working methods implemented in those libraries influenced the local community and how they were adopted.
Keywords: ekologija; Slovenija; splošne knjižnice; trajnostni razvoj; varstvo okolja; zelene knjižnice